Cystic Lung Disease in Down Syndrome: A Case Report and Literature Review. (3rd October 2016) - George, Mathew; Amodio, John; Lee, Haesoon
Abstract : Subpleural lung cysts (SPC) are seen in children with Down syndrome (DS). The incidence and the long term course of these lesions are not known. It is important for pediatricians and pediatric radiologists to be aware of these lung lesions since the DS patients' longevity has increased and they have greater frequency to encounter the clinicians. Autopsy and the radiology series have shown that these lesions are often found in association with congenital heart disease, particularly the endocardial cushion defect and prematurity.